Création lexicale et créativité textuelle: cas du figement et du défigement - Zhu, Lichao (Neophilologica, 2011)
A frozen sequence is a lexical creation. It draws its specificity from the construction of the text. We have tried to demonstrate how an “anti-process”, i.e. de-freezing would undo the language rules. We also establish a typological scheme of different processes of de-freezing and different influences brought to textual creativity. We try to illustrate these two linguistic processes with appropriate examples.